Additive-optimized micro-structure in cellulose acetate butyrate-based reverse osmosis membrane for desalination. (June 2023) - Liu, Jingjing; Qin, Xiang; Feng, Xiaoping; Li, Fengming; Liang, Jun; Hu, Dongying
Abstract: Progress toward the high water flux of cellulose acetate butyrate (CAB)-based reverse osmosis (RO) membrane is a bottleneck for desalination and mitigation of fresh water shortage. Here, we develop an "optimization of formulation-induced structure" strategy using acetone (solvent), triethyl phosphate (pore-inducing agent), glycerin and n-propanol (boosters), which achieves a state-of-the-art salt rejection of 97.1% and permeate flux of 8.73 L m −2 ·h −1, ranking top among CAB-based RO membrane. Compared with reported literatures, it represents high separation performance for different concentrations (20–100 mg L −1 ) of Rhodamine B and Congo red, different ion types (NaCl and MgCl2 ), different time (600 min), and resistance to feed pressure changes. The key is the appropriate viscosity of the casting solution (995.52 mPa s), the synergy between the components and additives, contributing to the formation of "jellyfish"-like microscopic pore structure with the lowest surface roughness (Ra = 16.3) and good hydrophilicity. The proposed correlation mechanism between additive-optimized micro-structure and desalination provides a promising prospect for CAB-based RO membrane. Graphical abstract: Image 1 Highlights: An "optimization of formulation-induced structure" strategy was adopted. Separation properties-good CAB-based RO membrane was fabricated. "jellyfish"-like microscopic structure show low surface roughness and good hydrophilicity. It achieved a state-of-the-art salt rejection of 97.1% and permeate flux of 8.73 L m −2 h −1 . The synergies between components and additives for enhanced properties were studied.